2016
DOI: 10.1126/science.aaf3621
|View full text |Cite
|
Sign up to set email alerts
|

Slow waves, sharp waves, ripples, and REM in sleeping dragons

Abstract: Sleep has been described in animals ranging from worms to humans. Yet the electrophysiological characteristics of brain sleep, such as slow-wave (SW) and rapid eye movement (REM) activities, are thought to be restricted to mammals and birds. Recording from the brain of a lizard, the Australian dragon Pogona vitticeps, we identified SW and REM sleep patterns, thus pushing back the probable evolution of these dynamics at least to the emergence of amniotes. The SW and REM sleep patterns that we observed in lizard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
172
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(194 citation statements)
references
References 48 publications
10
172
0
Order By: Relevance
“…Whereas the reptilian hippocampus possesses many fewer recognizable areas than that of mammals, the significance of this difference is at present unknown. It is our hope that, by combining modern anatomical, molecular, and electrophysiological techniques in multiple reptilian species [Shein-Idelson et al, 2016, 2017Tosches et al, in preparation], important questions concerning cortex and hippocampal evolution and function will be answered. Doody JS, Burghardt GM, Dinets V (2013) …”
Section: Discussionmentioning
confidence: 99%
“…Whereas the reptilian hippocampus possesses many fewer recognizable areas than that of mammals, the significance of this difference is at present unknown. It is our hope that, by combining modern anatomical, molecular, and electrophysiological techniques in multiple reptilian species [Shein-Idelson et al, 2016, 2017Tosches et al, in preparation], important questions concerning cortex and hippocampal evolution and function will be answered. Doody JS, Burghardt GM, Dinets V (2013) …”
Section: Discussionmentioning
confidence: 99%
“…Sleep is found to be universal in all animals studied, 37 essential to life, 38,39 and important to development 40,41 ; yet there are reports of constant locomotion behaviors in dolphins, 42 whale calves, 43 and migrating birds. 44 Although these studies do not show electrophysiological evidence of sleep, some authors posit that unihemispheric sleep is likely 45,46 and that migratory birds must somehow sleep in flight.…”
Section: Broader Implications Of the Findingsmentioning
confidence: 99%
“…Birds and nonavian reptiles are members of the Sauropsida whereas mammals are members of Synapsida, clades that last shared a common ancestor over 300 million years ago. Whether the presence of SWS and REM sleep in such evolutionarily distant groups is the result of convergent evolution or these states were present in, and inherited from, a common ancestor is still a subject of debate [Libourel and Herrel, 2015;Shein-Idelson et al, 2016]. Obviously, studies of the sleep patterns of nonavian reptiles and the anamniote out-group to amniotes (amphibians) are required to resolve this question.…”
Section: Evolution Of Sws and Rem Sleep: Convergence Or Inheritance?mentioning
confidence: 99%
“…Behaviors suggestive of REM sleep, including eye movements under closed eyelids and myoclonic twitches, have been observed across a variety of reptilian groups, in some cases accompanied by wake-like EEG activity [Tauber et al, 1966;Ayala-Guerrero and Vargas Reyna, 1987;Ayala-Guerrero et al, 1988;Shein-Idelson et al, 2016;reviewed in Hartse, 1994;Libourel and Herrel, 2015]. However, because arousal thresholds were not assessed during these periods, it remains unclear whether they reflect REM sleep or partial awakenings [Hartse, 1994;Libourel and Herrel, 2015;Shein-Idelson et al, 2016]. In addition, several studies in lizards, turtles, and crocodilians have not found REM sleep [Hartse, 1994;Eiland et al, 2001;Libourel and Herrel, 2015].…”
Section: Evolution Of Sws and Rem Sleep: Convergence Or Inheritance?mentioning
confidence: 99%
See 1 more Smart Citation